ANKARA EXHIBITION HOUSE BUILT IN THE STYLE OF DE STIJL MOVEMENT - İLKHAN SÖYLEMEZ , Duygu (SSD Journal, 2022)
De Stijl and Neoplasticism are two currents that are confused with each other. However, De Stijl emerged as an extension of Neoplasticism and influenced the following movements such as Futurism, Dadaism and Minimalism, and had an impact on the emergence of abstract art, especially in plastic arts and painting. In this movement, besides the use of straight horizontal and vertical lines, the use of the primary colors red, yellow and blue is frequently seen. The idea and purpose of living in art integrated with life caused De Stijl artists to focus on the art of architecture. In this trend, building units were built in which functionality is prominent, horizontal-verticality is emphasized, and with the materials and technology of the day, which can meet the needs of human beings. In the first period of the Republic, new architectural understandings began to be adopted in accordance with both Atatürk's will and industrial developments. As a result of these developments, although the emergence of the De Stijl movement and its entry into the Anatolian lands were simultaneously, it was observed that it mixed with other styles as well as alone in Turkey. With the Ankara Exhibition House, which was built with the De Stijl movement, universal tools were embodied, and a link was established between art and rational life. In a sense, the harmony of modern art with modern life has been realized.